NILAI MORAL DALAM NOVEL HIJRAH TERINDAH KARYA INDAHNURSF DAN JAYMES R - Wahyuni; Yunus Yunus; La Ode Balawa (Jurnal Bastra (Bahasa dan Sastra), 2025)
The problem of this research is what moral values ​​are contained in the novel Hijrah Terindah by Indahnursf and Jaymes R? The aim of this research is to describe and analyze the moral values ​​in the novel Hijrah Terindah by Indahnursf and Jaymes R. This research uses qualitative descriptive methods, and the data used are texts, words and sentences related to moral values ​​sourced from the novel The Most Hijrah Terindah by Indahnursf and Jaymes R, published by Aksara Plus, Jakarta, 2020 with 206 pages. The data collection technique for this research is note-taking and critical reading techniques which are carried out by reading and recording quotations which relates to the moral values ​​contained in the novel Hijrah Terindah by Indahnursf and Jaymes R. The data analysis technique uses a moral approach. The results of the analysis show that man's relationship with God is in the form of; feelings of sin against God, praying or begging God, recognizing the greatness of God, religious feelings, and obedient worship. Moral values ​​in human relations with themselves are in the form of; self-existence, fear, self-esteem, and patience. Moral values ​​in human relations with humans in the social sphere are in the form of; think positively, help others, help the weak selflessly, and get to know each other. Moral values ​​in human relations with nature are in the form of; utilization of natural resources.